Structure‐function analysis for the development of peptide inhibitors for a Gram‐positive quorum sensing system. Issue 6 (28th May 2022) - Abdullah, Iman Tajer; Ulijasz, Andrew T.; Girija, Umakhanth Venkatraman; Tam, Sien; Andrew, Peter; Hiller, Natalia Luisa; Wallis, Russell; Yesilkaya, Hasan
Abstract: The Streptococcus pneumoniae Rgg144/SHP144 regulator‐peptide quorum sensing (QS) system is critical for nutrient utilization, oxidative stress response, and virulence. Here, we characterized this system by assessing the importance of each residue within the active short hydrophobic peptide (SHP) by alanine‐scanning mutagenesis and testing the resulting peptides for receptor binding and activation of the receptor. Interestingly, several of the mutations had little effect on binding to Rgg144 but reduced transcriptional activation appreciably. In particular, a proline substitution (P21A) reduced transcriptional activation by 29‐fold but bound with a 3‐fold higher affinity than the wild‐type SHP. Consistent with the function of Rgg144, the mutant peptide led to decreased utilization of mannose and increased susceptibility to superoxide generator paraquat. Pangenome comparison showed full conservation of P21 across SHP144 allelic variants. Crystallization of Rgg144 in the absence of peptide revealed a comparable structure to the DNA bound and free forms of its homologs suggesting similar mechanisms of activation. Together, these analyses identify key interactions in a critical pneumococcal QS system. Further manipulation of the SHP has the potential to facilitate the development of inhibitors that are functional across strains. The approach described here is likely to be effective across QS systems in multiple species. Abstract : Streptococcus pneumoniae utilizes a network of cell‐cell communication molecules to respond to extracellular cues. The regulator‐peptide system, Rgg144/SHP144, plays a central role in this network, making it a major virulence determinant. Here we employ structure‐function studies to identify residues that contribute to the affinity and activities of Rgg144 signalling that in turn modulate pneumococcal pathogenesis.